Introducing Economic Sociology - Ричард Сведберг; Нил Смелсер (Journal of Economic Sociology, 2010)
Here by the main part of the « Introducing Economic Sociology» is given. This is the introduction paper to the most famous nowadays reader on economic sociology – «The Handbook of Economic Sociology» (1994). This text gives the definition of the economic sociology, as well as the comparison of the economic sociology and the mainstream economics. This paper also provides the analysis of such issues as term of actor, term of economic action, limits of economic action, and relation of economics toward society. The authors compare goals, methods and intellectual traditions of the discussed approaches.